Lead nitroprusside: A new precursor for the synthesis of the multiferroic Pb2Fe2O5, an anion-deficient perovskite - Gil, Diego Mauricio (2013)
In order to investigate the formation of multiferroic oxide Pb2Fe2O5, the thermal decomposition of Pb[Fe(CN)5NO] has been studied. The complex precursor and the thermal decomposition products were characterized by IR and Raman spectroscopy, thermal analysis, powder X-ray diffraction (PXRD), scanning electron microscopy and magnetic measurements. The crystal structure of Pb[Fe(CN)5NO] was refined by Rietveld analysis. It crystallizes in the orthorhombic system, space group Pnma. The thermal  decomposition in air produces highly pure Pb2Fe2O5 as final product. This oxide is an anion deficient perovskite with an incommensurate superstructure. The magnetic measurements confirm that Pb2Fe2O5 shows a weak ferromagnetic signal probably due to disorder in the perfect antiferromagnetic structure or spin canting. The estimated ordering temperature from the fit of a phenomenological model was 520 K. The SEM images reveal that the thermal decomposition of Pb[Fe(CN)5NO] produces Pb2Fe2O5 with small particle size.